Wogonin increases gemcitabine sensitivity in pancreatic cancer by inhibiting Akt pathway - Zhang, Tianli; Liu, Mengmeng; Liu, Qing; Xiao, Gary Guishan (Frontiers in Pharmacology, 2022)
Pancreatic cancer has a high degree of malignancy and a low five-year survival rate, and drug resistance is one of the main factors leading to poor prognosis of pancreatic cancer. Wogonin is a flavonoid drug isolated from Scutellaria baicalensis, which has certain antitumor activity. Hence the purpose of this study was to investigate whether wogonin can be used to enhance the sensitivity of pancreatic cancer to gemcitabine chemotherapy, and investigate its possible sensitization mechanism. In vitro, MTT assay showed that wogonin increased gemcitabine cytotoxicity in gemcitabine-resistant pancreatic cancer cells. in vivo, Wogonin combined with gemcitabine was found to inhibit tumor growth in orthotopic pancreatic cancer mouse model. In order to explore the sensitization mechanism, the differentially expressed genes (DEGs) of the gemcitabine-resistant cell line Panc-1 and the gemcitabine-sensitive cell line Bxpc-3 were screened through the GEO database, and 15 DEGs were obtained by intersecting with the potential targets of wogonin. GO and KEGG enrichment analysis was performed. Bioinformatics results predicted that wogonin promoted pancreatic cancer cell apoptosis by inhibiting protein kinase B (Akt) signaling, thereby enhancing the sensitivity of gemcitabine to Pancreatic cancer. The above results were also verified by flow cytometry and Western blotting experiments. In conclusion, wogonin may enhance the sensitivity of gemcitabine by inhibiting Akt pathway.